Teleultrasonido ocular durante la pandemia de COVID-19 - Mariana Mayorquín-Ruiz; Ana P. Bustamante-Vargas; Catalina Becerra-Revollo; Carlos Ríos-Elizondo; David Berrones-Medina; Gerardo M. Hernández-Valero; Samuel Peña-Ortiz; Mariam Cernichiaro-Espinosa (Revista Mexicana de Oftalmología)
Objective: To determine the concordance in ultrasound diagnoses made by an ophthalmologist who is not an expert in ocular ultrasound (ONE) guided virtually by an expert in ocular ultrasound (EUO1) and those made by a second expert in ocular ultrasound (EUO2). Method: Observational, cross-sectional study. Patients referred to the ocular ultrasound service with media opacity were reviewed. The ONE performed the ultrasound study guided virtually by an EUO1. Subsequently, an EUO2 performed an ultrasound study on the same patient. Diagnoses and ultrasound findings of both were analyzed in a database. Results: We included 41 eyes of 24 patients referred to the ocular ultrasound service. The concordance between the ONE virtually guided by an EUO1 and the EUO2 was very high in the variables: ocular biometry, phakic state of the eye, presence of silicone in the vitreous cavity, presence of staphyloma, retinal and choroidal detachment. The variables with the least strength of correlation were: presence of posterior hyphema, description of optic nerve excavation and presence of hyaloid adhesion to the posterior pole. Conclusions: The high concordance between the ONE guided virtually by EUO1 and the EUO2, shows the possibility of developing mentoring and interconsultation through tele-ultrasound.